Parametric Method for Evaluation of Risk Changes in Power System Break-Down Origin - Y. V. Kalentionok; Y. D. Filipchik (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика, 2008)
The paper presents a method for evaluation of risk changes in power system break-down origin with the help of monitoring parameters of power system operation. Quantitative evaluation has been executed on the basis of 17 power system indices and it has been shown that risk value of break-down origin is fluctuating close to a mean value in spite of increases in power station and substation equipment wear and break-down portion due to its ageing.